NURSES’ PERCEPTION ABOUT RESPONSIBILITY OF CARE IN DECUBITUS ULCER MANAGEMENT - SUYASA, I GEDE PUTU DARMA (Nurse Media Journal of Nursing, 2007)
This study was conducted in order to increase the understanding of issues around decubitus ulcer care in the Indonesian context. The study identified Indonesian nurses’ perception regarding responsibility of care in the area of decubitus ulcer management. The choice of a qualitative research approach to elucidate the research questions provides the most appropriate way to fully appreciate and understand the uniqueness of the participants’ view. In this study, eight nurses were interviewed using semi-structured interviews. Two themes arose from the study include nurses’ responsibility and family involvement. In maintaining the quality of care in the decubitus ulcer area, the participants in this study emphasised the significance of the caring responsibility of both nurses and family. Appropriate education and adequate training for the family are essential in ensuring quality care when involving the family in giving any direct care to hospitalised patients.